Straight line methods for estimating permeability or width for a two-zone composite channelized reservoir - Escobar, Freddy Humberto; Montealegre Madero, Matilde; Carrillo Moreno, Daniel (CT&F - Ciencia, Tecnología y Futuro, 2009)
Some well pressure tests conducted in channelized systems which result from either fluvial deposition or faulting, cannot be completely interpreted by conventional techniques, since variation in facies or reservoir width are not normally recognized yet in the oil literature. In this case, the corresponding equations traditionally used for singlelinear flow will provide inaccurate results. Therefore, they must be corrected. In this study, new equations to be used in conventional analysis for the linear flow (pseudo linear) regime formed during the acting of the anomaly - reservoir width or permeability - are introduced to the oil literature. The equations do not consider the simultaneous variation of both parameters. The proposed equations were validated by applying them to synthetic and field examples.